Sensitivity analysis for variable dynamic load parameters - Garstecki, Andrzej; Pozorski, Zbigniew (Computer Assisted Methods in Engineering and Science, 2023)
The paper is concerned with a class of generalized structural optimization problems for which not only stiffness, damping and mass parameters but also loading and support parameters are unspecified and subject to sensitivity analysis and optimization. Both, viscous and complex modulus damping models are used. Single concentrated force and coupling of a force with a concentrated moment, which lags by ᴫ/2, are considered. The latter case corresponds to an excitation induced by a rotational machine with eccentricity. Steady-state periodic vibrations are studied. Response functionals in the form of displacement amplitudes are discussed. Numerical examples of beam and plate structures illustrate the theory and demonstrate the accuracy of the derived formulae for sensitivity operators.